Report on production of Orange Fleshed Sweetpotato early generation seed and multiplication by farmers in Malawi - International Potato Center (International Potato Center, 2023)
This report present progress and achievement of the seed multiplication activities under the Ukama Ustawi (UU) regional initiative in Malawi. International potato Center and its key research partner, Department of Agriculture and Research services (DARS) has been carrying out sweetpotato early generation seed (EGS) multiplication at Bvumbwe research stations. Early generation seed multiplication for Four (4) Orange fleshed sweetpotato (OFSP) varieties have been conducted in the greenhouse producing almost 80 bundles that have been distributed to community-based seed multipliers for further multiplication. Up to this reporting period, 40 farmers have been trained on vine multiplication through UU support. The total number of farmers have produced and supplied 1800 bundles each of 100 cuttings of 30cm long to vulnerable . Additional number of trained multipliers commence multiplication shortly.